2021
DOI: 10.1186/s12913-021-06725-5
|View full text |Cite
|
Sign up to set email alerts
|

Health service underutilization and its associated factors for chronic diseases patients in poverty-stricken areas in China: a multilevel analysis

Abstract: Background Underutilization of health services among chronic non-communicable disease sufferers, especially for hypertension (HBP) and diabetes mellitus (DM), was considered as a significant contributing factor to substantial cases in terms of both avoidable morbidity and mortality. However, evidence on health services underutilization and its associated factors in poverty-stricken areas remain scarce based on previous literature. This study aims to describe health services underutilization for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…We also found that male respondents and those who were married, older, completed primary or secondary school education, and lived in a small (≤2 members) household were more likely to incur CHE. These factors are usually labeled as predisposing factors for healthcare services use ( 13 , 59 ). For example, education can improve health literacy and encourage use of healthcare services ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that male respondents and those who were married, older, completed primary or secondary school education, and lived in a small (≤2 members) household were more likely to incur CHE. These factors are usually labeled as predisposing factors for healthcare services use ( 13 , 59 ). For example, education can improve health literacy and encourage use of healthcare services ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Health service use reflects individual behaviors related to obtaining health services to meet their health demands. Existing literature has shown that health service use is affected by individual demographic and socioeconomic factors such as age, gender, marital and employment status, education level, insurance, income ( 13 ), and health care system characteristics such as the availability, affordability, and accessibility of drugs and healthcare services ( 14 ). Previous studies have reported that health service use among cancer patients differs by sex, age, residence, employment, education, health insurance, household income, tumor site, and tumor stage ( 15 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…We think our early warning model is practical and down-to-earth in rural China. As the largest developing country confronted with underdeveloped healthcare systems and aging population ( 41 ), China is struggling to address the issue of health care coverage in rural areas. Despite the tremendous achievements in health care in rural China over the past 30 years, the problem of “difficult and expensive access to health care” still exists in the countryside.…”
Section: Discussionmentioning
confidence: 99%